Catholic theology of revelation on the eve of Vatican II : a redaction history of the schema De fontibus revelationis (1960-1962) - Schelkens, K. (Karim) (Leiden ; Boston : Brill, 2010)
In recent literature on the history of the Second Vatican Council, the schema "De fontibus revelationis" is a constant point of reference. In most cases, its utter rejection during the conciliar debate on revelation, biblical exegesis, and the nature of Scripture and Tradition, is regarded as a milestone for the council's development. This book is devoted to the background, genesis, and evolution of that very document, and offers a critical revision of the way in which the document has been received in conciliar historiography, based upon a study of archival material. The result is a.
Acknowledgements; Abbreviations; Introduction; Chapter One Preconciliar Vota and their Background; Chapter Two The Preparatory Theological Commission; Chapter Three The Schema Compendiosum; Chapter Four Historicity, Inspiration and Inerrancy (January 1961); Chapter Five Scripture and Tradition (June 1961); Chapter Six The Final Draft: Reception; CONCLUSIONS; SOURCES; INDEX OF NAMES.
Includes bibliographical references (pages 281-287) and index.
Print version record.
Master record variable field(s) change: 610, 611, 650
Keywords: Catholic Church -- Doctrines -- History -- 20th century; Catholic Church; Vatikanisches Konzil (1962-1965); Dei Verbum; Revelation -- Catholic Church -- History of doctrines -- 20th century; RELIGION -- Christian Theology -- Ecclesiology; Theology, Doctrinal; Offenbarung; Theologie; Vorgeschichte; 1900-1999; Electronic books; History